How Much Life do I Lose from the Plague? Educational Board Games as Teaching Tools in Archaeology and Ancient History Courses. (3rd April 2015) - Huffer, Damien; Oxenham, Marc
Abstract : This article describes the development, implementation, assessment, debriefing and outcomes, and potential uses of a university student-driven educational gaming project, as a major assessment item in an archaeology course entitled 'Ancient Medicine'. Discussion of these various aspects of the project is explored in the context of educational gaming theory and practice. We demonstrate that educational board games not only represent an effective method for students to retain and convey information in courses exploring the history and archaeology of medicine, but provide such a platform for undergraduate courses in general. Furthermore, we argue that they can present a cost-effective, fun and less time-/resource-intensive alternative to electronic or web-based projects, while still being an attractive addition to traditional classroom teaching methods.